Precarious Lives Forced labour, exploitation and asylum - Lewis, Hannah (2014)
Available Open Access under CC-BY-NC-ND licence This ground breaking book presents the first evidence of forced labour among displaced migrants who seek refuge in the UK. Through a critical engagement with contemporary debates about precarity, unfreedom and socio-legal status, the book explores how asylum and forced labour are linked, and enmeshed in a broader picture of modern slavery produced through globalised working conditions. Drawing on original evidence generated in fieldwork with refugees and asylum seekers, this is important reading for students and academics in social policy, social geography, sociology, politics, refugee, labour and migration studies, and policy makers and practitioners working to support migrants and tackle forced labour.